2019
DOI: 10.1080/22797254.2019.1683471
|View full text |Cite|
|
Sign up to set email alerts
|

UAV for monitoring the settlement of a landfill

Abstract: Remote-pilot aircraft are developing very rapidly and their potential in the various fields is often still to be fully investigated. The possibility to fly over the areas to be surveyed without the need to access the areas themselves makes the use of UAVs in some cases certainly preferable for safety reasons, as has already been tested for the management of postdisaster areas. Waste landfills are small sites where contact with waste itself must be limited and scientific experimentation on surveying this specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The RTK/PPK method is less influenced by onboard flight patterns, vegetation phenology, and data post-processing. Notably, the RTK/PPK method succeeds in surveying inaccessible or hazardous terrains, such as dense forests [72], volcano tectonics [78], or settlement landfills [79] and ice sheets [80,81]. A recent study by Zhang et al [82] showed that the PPK method can provide the same accuracy as the use of GCPs, with a small variation in vertical accuracy, which could be solved by including only one GCP.…”
Section: Georeferencingmentioning
confidence: 99%
“…The RTK/PPK method is less influenced by onboard flight patterns, vegetation phenology, and data post-processing. Notably, the RTK/PPK method succeeds in surveying inaccessible or hazardous terrains, such as dense forests [72], volcano tectonics [78], or settlement landfills [79] and ice sheets [80,81]. A recent study by Zhang et al [82] showed that the PPK method can provide the same accuracy as the use of GCPs, with a small variation in vertical accuracy, which could be solved by including only one GCP.…”
Section: Georeferencingmentioning
confidence: 99%
“…The network helped in defining failure endangered zones, for which the approach of the observational method was applied. It allowed the analysis of the vertical and horizontal displacement measurements of the landfill body during exploitation time [24,25]. This type of monitoring system allowed the evaluation of the behavior of all slope movement influenced by different groundwater flow conditions, and engineering works execution.…”
Section: Slope Stability Analyses Incorporating Reinforcementsmentioning
confidence: 99%
“…The development of unmanned aerial vehicle (UAV) photogrammetry has allowed researchers to obtain high-resolution orthophoto maps and digital surface models (DSMs) in a more flexible way compared to InSAR. The capacity of UAV has been demonstrated in recent studies involving landslide monitoring [16][17][18]. Site images acquired by drones can be processed with structure from motion (SFM) methods and multi-image approaches to identify the geomorphological changes in hazardous bodies [18].…”
Section: Introductionmentioning
confidence: 99%